THE SOCIOLOGY OF PUNISHMENT: SOCIETAL DYNAMICS AND MODERN CRIMINAL POLICY - Kayumova Farzona Khayrulla kizi,; Salayev Nodirbek Saparbayevich, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract This scientific article explores the complex phenomenon of criminal punishment through the analytical lens of the sociology of punishment. Traditionally, penal institutions have been evaluated either through a penological framework focused strictly on crime control or a philosophical framework concerned with moral justifications. However, these approaches often fail to capture the broader social determinants and consequences of penal practices. By synthesizing the foundational sociological theories of Emile Durkheim, Karl Marx, Michel Foucault, and Norbert Elias, this article demonstrates that punishment is a deeply embedded social institution shaped by cultural sensibilities, economic structures, and technologies of power. Furthermore, the study conducts a comparative analysis of modern penal policies, contrasting the harsh, exclusionary practices of American mass incarceration with the reintegrative, humane approaches found in European systems. The findings emphasize that the true social efficiency of criminal policy relies not on the severity of sanctions, but on the capacity of the state to resocialize offenders, uphold human dignity, and maintain social solidarity.